Electricity market integration, decarbonisation and security of supply - Do, Hung,Nepal, Rabindra,Jamasb, Tooraj (Department of Economics, Copenhagen Business School, 2020)
This study investigates the volatility connectedness between the Irish and Great Britain electricity markets and how it is driven by changes in energy policy, institutional structures and political ideologies. We assess various aspects of this volatility connectedness including static (unconditional) vs dynamic (conditional), symmetric vs asymmetric characteristics between 2009 and 2018. We find that volatility connectedness is time varying and is significantly affected by important events, policy reforms or market redesigns such as Brexit, oil price slump, increasing share of renewables, and fluctuations in the exchange rates. Our asymmetric analysis shows that the magnitude of the good volatility connectedness is marginally larger than that of the bad volatility connectedness. Our result suggests that good volatility levels would be even higher once the Irish market adopts the carbon price floor. Therefore, supporting renewable generation by setting an appropriate carbon price in interconnected wholesale electricity markets will improve market integration.
10398/9792
Keywords: Graue Literatur; Market integration; electricity; renewable; energy policy; volatility